Reforming Massacre. Issue 1 (2nd January 2017) - Lucas, Kristin
Abstract : Marlowe's The Massacre at Paris is known for having a fractured perspective, which nullifies difference between Protestant and Catholic factions. The troubling instability of Marlowe's play is brought into focus by attending to medieval representations of massacre, namely the Slaughter of the Innocents. In medieval pageants, Herod's massacre is aligned with Christ's escape into Egypt, and sometimes with Herod's own hellish demise. As such, massacre is absorbed into sacred order. In Marlowe's The Massacre at Paris, the cohesive perspective of the earlier drama is in turn suggested and suppressed. In diction and structure, Marlowe's play alludes to the Slaughter of the Innocents and the teleological pattern found in the middle ages. But instead of paving the way for redemption, the Guise's atrocity brings only further bloodshed. Substituting factional violence for salvation, The Massacre at Paris enacts the tremendous social rifts brought about by the Reformation, and underscores the need for a considered response to state violence.